Manganese catalyzed dehydrogenative silylation of alkenes: Direct access to allylsilanes. Issue 26 (25th June 2020) - Wu, Shang; Zhang, Ying; Jiang, Hongyan; Ding, Ning; Wang, Yanbin; Su, Qiong; Zhang, Hong; Wu, Lan; Yang, Quanlu
Graphical abstract: We have reported an example of dehydrogenative coupling of allyl arenes with silanes enabled by a commercial available Mn2 (CO)10 complex catalysis. Highlights: Manganese catalyzed dehydrogenative silylation of alkenes with silanes. Silane radicals initiated by manganese complex without additional oxidants. Convenient and practical protocol for the modular synthesis of allylsilanes. Abstract: Dehydrogenative silylation of alkenes with silanes to produce allylsilanes is achieved through manganese catalysis with a wide scope of substrate tolerance. This transformation involves silane radicals initiated by manganese complex without additional oxidant additives. It offers a general, convenient and practical protocol with excellent functional group compatibility and gram-scale capacity for the modular synthesis of allylsilanes.